PENGARUH INFLASI, BI RATE, DAN JUMLAH UANG BEREDAR TERHADAP DANA PIHAK KETIGA PERBANKAN SYARI’AH DI INDONESIA PERIODE 2005 – 2015 - Rifqi Maulana (EPI 16 UMY 117, 2016)
*117 This research aims to analyze the influence of macroeconomics variables consisting of inflation, interest rate in BI rate, and the money supply toward the third-party funds of sharia banking in Indonesia especially in mudharabah savings. By finding out which variables of macroeconomics changes in Indonesia. The research type is quantitative research By using data time series in the period of january 2005-Desember 2015. The analysis technique used in This research uses multiple linier regressions with SPSS to find out the influence of macroeconomics variables consisting of inflation, intereset rate of BI rate, and the money supply toward the third-party funds of sharia banking in Indonesia especially in mudharabah savings. The research results show that the variables of inflation and interest rate in BI rate has positive but insignificant toward the third-party funds of sharia banking in Indonesia especially in mudharabah savings. The independent variables are stated of influencing the investment risk if the sig. Value <0.05. Inflation has the sig. value of 0.604 and interest rate has the sig. value 0.523. Meanwhile, the money supply variable has positive and significant influence with the sig. value of 0.001. Keywords: Inflation, Money Supply, Interest rate in BI rate, Third-party Funds, mudharabah savings.